Helene Simoni, Geographical Information Systems in Urban Archaeology and Urban Planning. A case study of a modern Greek city, built on top of an ancient city. (British Archaeological Reports 2812). - Sbonias, Kostas (Journal of Greek Archaeology, 2023)
pp. 83, 36 tables, 35 figures. Oxford: BAR Publishing, 2016. ISBN 978140731477-8 paperback, £25.00.